Analisis Pengaruh Indeks Pembangunan Manusia Dan Tingkat Pengangguran Terbuka Terhadap Penduduk Miskin Di Provinsi Sumatera Barat - Raldo, Alfio; Samsuddin, M. Afdal (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
Poverty remains a fundamental challenge in national development, particularly in developing countries such as Indonesia. This study aims to examine the influence of the Human Development Index (HDI) and the Open Unemployment Rate (OUR) on the percentage of poor population (PP) in West Sumatra Province. Employing a quantitative associative approach, this research utilizes annual secondary data from 1994 to 2023. The analysis method used is multiple linear regression, supported by classical assumption tests and hypothesis testing, including t-tests, F-tests, and the coefficient of determination. The results indicate that, partially, HDI has a significant negative effect on PP, suggesting that improvements in human development contribute to poverty reduction. On the other hand, OUR does not show a statistically significant effect on PP, although it tends to have a negative relationship. Simultaneously, HDI and OUR have a significant joint effect on PP, with an Adjusted R² value of 0.989, indicating a very high predictive capability of the model. These findings offer critical insights for the formulation of inclusive, data-driven socio-economic policies at the provincial level.